Optimization of air suspension system for improved ride and handling performance in road vehicles dynamic - Armansyah, Armansyah; Keshavarzi, Ahmad; Kolahdooz, Amin; Ferdyanto, Ferdyanto; Mardhani, Muhammad Destri (Mechanical Engineering for Society and Industry, 2024)
This study focused on the optimization of air suspension systems (ASs) for road vehicles concerning on-ride and handling criteria. A quarter DOF vehicle model is used in this study to develop an optimized system based on nonlinear equations. The extracted equations are then linearized and transformed into dimensionless form to gain insights into the system's behavior. By employing the Root-Mean-Square (RMS) method, the dimensionless equations are utilized to optimize the system parameters focused on stability and ride comfort. The five main components are attached in the model which consisted of the sprung mass (SM), unsprung mass (USM), gas spring (GS), auxiliary reservoir (AR), and orifice (O). The optimization procedure involved adjustment to the orifice resistance coefficient, air spring volume, air spring area, and auxiliary volume using the RMS-based method. Simulation analysis revealed the superior performance of the RMS-optimized system in both ride quality and handling. The study concludes by emphasizing the advantages of utilizing the RMS method for optimizing air suspension, resulting in decreased sprung mass acceleration and enhanced handling qualities. Selecting the appropriate design point for the suspension system based on the method outlined in this article can ensure both stability and comfort in the vehicle simultaneously.